Segmentation of Skin Lesions Using Level Set Method - Zhen Ma (2014)
Diagnosis of skin cancers with dermoscopy has been widely accepted as a clinical routine. However, the diagnostic accuracy using dermoscopy relies on the subjective judgment of the dermatologist. To solve this problem, a computer-aided diagnosis system is demanded. Here, we propose a level set method to fulfill the segmentation of skin lesions presented in dermoscopic images. The differences between normal skin and skin lesions in the color channels are combined to define the speed function, with which the evolving curve can be guided to reach the boundary of skin lesions. The proposed algorithm is robust against the influences of noise, hair, and skin textures, and provides a flexible way for segmentation. Numerical experiments demonstrated the effectiveness of the novel algorithm.